“A WAY OUT OF NO WAY”: A NOTE ON THE BACKGROUND OF THE AFRICAN AMERICAN PROVERBIAL SAYING - Doyle, Charles Clay (Proverbium - Yearbook, 2014)
The proverbial phrase “make a way out of no way,” common in the rhetoric of Martin Luther King and other African American writers and speakers in the twentieth century, was anticipated by very similar expressions among nineteenth-century Quakers—and before that by a sixteenth century Protestant Reformer.